Pengaruh Shopping Lifestyle Dan Fashion Involvement Terhadap Impulse Buying Shopee Pada Gen Z di DIY - Anisyah Vira Saputri Imran; Wina Driyan Pradana (STIKes Ibnu Sina Ajibarang, 2024)
Impulse buying is a situation where consumers carry out the shopping process without any prior plans or it happens suddenly. DIY is the area with the highest internet users on the island of Java and its population is dominated by Gen Z. Gen Z is a generation that grew up with the development of existing technology and always follows the development of existing trends. The presence of e-commerce makes it easier for Gen Z to carry out the shopping process which can be accessed easily. Factors that cause this impulse buying behavior include shopping lifestyle and fashion involvement. This research aims to determine the influence of shopping lifestyle and fashion involvement on impulse buying at Shopee. This research uses explanatory research with a quantitative approach using a sampling technique using the purposive sampling method. Data was taken using an online questionnaire from 200 respondents. Data analysis in this study was assisted by SPSS version 27 software. The results of this research show that the shopping lifestyle that consumers have and fashion involvement or consumer involvement in the fashion products offered by shops is increasingly developing following existing trends, which can lead to impulse buying in consumers. The conclusion is that the variables shopping lifestyle and fashion involvement influence impulse buying at Shopee.